A comparative biomechanical analysis of the performance level on chasse step in table tennis. Issue 3 (June 2019) - Yu, Changxiao; Shao, Shirui; Baker, Julien S; Awrejcewicz, Jan; Gu, Yaodong
Initial observations have indicated that each movement pattern or skill set has a fundamental mechanical structure. The purpose of this study was to examine biomechanical characteristics in the chasse step movement patterns between professional athletes (PA) and beginner players (BP). Large data sets were obtained for comparison by capturing kinematic and kinetic information of the dominant foot using the Oxford Foot Model (OFM) during table tennis strokes. Nine male PA and nine BP (all with dominant right feet) participated in a table tennis footwork test. A Vicon motion analysis system and a Novel Pedar insole plantar pressure measurement system were used to record kinematic and kinetic data, respectively. Findings from the study indicated that PA not only showed significantly larger forefoot and rear-foot dorsiflexion, but also demonstrated larger hallux plantarflexion. Also, PA showed significantly larger forefoot inversion and abduction at the forward-end of the step. Peak pressure values were higher under the lateral forefoot, and the medial and lateral rear-foot with faster changes in angular velocity recorded for PA during the chasse step phase. Greater peak pressures were also recorded under the other toes, and in the central and lateral forefoot during the forward swing phase when compared to BP. The results of the present study demonstrated that PA possessed greater foot drive technique. These findings may help coaches and beginners to comprehend the internal mechanisms of the chasse step technique and assist beginners in improving the mechanical efficiency of their performance.